Genetic diversity of Anaplasma bacteria: Twenty years later - Rar, Vera; Tkachev, Sergey; Tikunova, Nina (Infection, genetics and evolution, 2021)
The genus Anaplasma (family Anaplasmataceae, order Rickettsiales) includes obligate intracellular alphaproteobacteria that multiply within membrane-bound vacuoles and are transmitted by Ixodidae ticks to vertebrate hosts. Since the last reclassification of Anaplasmataceae twenty years ago, two new Anaplasma species have been identified. To date, the genus includes eight Anaplasma species (A. phagocytophilum, A. marginale, A. centrale, A. ovis, A. bovis, A. platys, A. odocoilei, and A. capra) and a large number of unclassified genovariants that cannot be assigned to known species. Members of the genus can cause infection in humans and a wide range of domestic animals with different degrees of severity. Long-term persistence which, in some cases, is manifested as cyclic bacteremia has been demonstrated for several Anaplasma species. Zoonotic potential has been shown for A. phagocytophilum, the agent of human granulocytic anaplasmosis, and for some other Anaplasma spp. that suggests a broader medical relevance of this genus. Genetic diversity of Anaplasma spp. has been intensively studied in recent years, and it has been shown that some Anaplasma spp. can be considered as a complex of genetically distinct lineages differing by geography, vectors, and host tropism. The aim of this review was to summarize the current knowledge concerning the natural history, pathogenic properties, and genetic diversity of Anaplasma spp. and some unclassified genovariants with particular attention to their genetic characteristics. The high genetic variability of Anaplasma spp. prompted us to conduct a detailed phylogenetic analysis for different Anaplasma species and unclassified genovariants, which were included in this review. The genotyping of unclassified genovariants has led to the identification of at least four distinct clades that might be considered in future as new candidate species. •A. phagocytophilum, A. ovis, A. bovis, A. platys, and A. capra can infect humans.•Ruminants are main reservoir hosts for most Anaplasma spp.•Some Anaplasma spp. can be considered as a complex of genetically distinct lineages.•Distinct enzootic cycles for A. phagocytophilum were recorded.•Four distinct clades were identified among Anaplasma spp. unclassified genovariants.